CURRICULUM: FUNCTION, RELATIONSHIP BETWEEN EDUCATION AND TEACHING - Akmal Akmal (CV. Adiba Aisha Amira, 2024)
The curriculum plays an important role in education both in educational institutions and in the community. The curriculum plays a role in shaping students ready to go into society. That way the curriculum must contain a conservative role so that students are able to transmit the cultural values of society so that students are able to preserve the cultural values of society and are not influenced by foreign cultures, creative roles so that students become more creative, innovative and constructive when facing various problems or conditions to be resolved and critical and evaluative roles so that students are able to filter cultural values that are still relevant to the times or conditions of society. The curriculum is closely related in education. Curriculum that is closely related in education. Where the curriculum is also a tool for developing education both through school education institutions, madrasas and Integrated Islamic Schools which have different educational goals. Where schools emphasize more knowledgeable students, madrasas that emphasize students have a strong religious foundation and the Integrated Islamic School emphasizes both broad knowledge which is fortified with strong religious knowledge.